PENGGERAKAN PROGRAM BAHASA ARAB DI PONDOK PESANTREN MODERN - Ahmadi, Maswan; Istita'ah, Kurnia; Sholihah, Nur Rohmah; Arifah, Zakiyah (Arabi : Journal of Arabic Studies, 2018)
The emergence of pesantrens that paid more attention to the Arabic language brings new hope in its development in Indonesia. Various Arabic programs are planned to improve the students' abilities in Arabic language. However, many Arabic programs do not work well because of the lack of ability to implement the program. The implementation has an important function in realizing the program that has been prepared. This implementation at least included leadership, communication, and supervision. The purpose of this research was to find an effective model of Arabic program implementation in modern boarding school. The method used was qualitative descriptive. The results showed that leadership, communication, and supervision determine whether or not the program was running.